Uji Efektivitas Ekstrak Daun Ketapang (Terminalia catappa) Untuk Pengobatan Benih Ikan Mas (Cyprinus carpio) Yang Diinfeksi Jamur Saprolegnia sp. - Yasani, Syuhrizal; Mulis, Mulis; Lamadi, Arafik; Fintarji, Rian (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2024)
This research aimed to determine the influence of usung ketapang leaf (Terminalia catappa) extract for treating common carp (Cyprinus carpio) seeds infected with Saprolegnia sp. fungus. The method employed in this study was an experiment. The test animals was used were common carp (Cyprinus carpio) seeds, totaling 225 individuals, divided into 5 treatments with 3 replications. In each treatment, 100 ppm ketapang leaf extract was administered was with different immersion duration, namely Treatment A (Control) B (3 hours of extract immersion), C (6 hours of extract immersion), D (9 hours of extract immersion), and E (12 hours of extract immersion). The treated common carp seeds were then raised in 15 aquariums with a volume 30 liters of water each, at a density of 1 individual per 2 liters, to observe healing time and survival rates. The research was conducted from August to September at the Tatelu Freshwater Aquaculture Research Institute. The research design used in this study was a Completely Randomized Design (CRD) using Analysis of Variance (ANOVA). Subsequently, post hoc tests were conducted using the Least Significant Difference (LSD) test. The results obtained indicated that the use of ketapang leaf (Terminalia catappa) extract signifucantly influences the treatment of common carp (Cyprinus carpio) seeds infected with Saprolegnia sp. Fungus. The best healing time is in Treatment E (6 days), D (7 days), C (9 days), B (10 days), and A (not healed). The highest survival rates are in Treatment E (57.78%), D (46.67%), C (31.11%), B (26.67%), and A (8.89%).